Inclusion Evolution and Estimation during Secondary Refining in Calcium Treated Aluminum Killed Steels. Issue 11 (20th March 2014) - Yang, Die; Wang, Xinhua; Yang, Guangwei; Wei, Pengyuan; He, Jinping
<x xml:space="preserve">Abstract</x> The objective of this study was to investigate the evolution of inclusions during secondary refining in aluminum killed steels. As calcium treatment is also used to modify solid alumina inclusions to liquid or partially liquid calcium aluminates for keeping free from nozzle clogging, a thermodynamic model has been calculated using Factsage to predict the type of calcium aluminates and sulfides present in the steel. The results showed that alumina generated from deoxidation had transformed to MgOAl2O3 spinel with a small amount of CaO by using high basicity and high Al2O3 slag during ladle furnace (LF) refining. Though soft blowing after LF refining is benefit for the removal of inclusions by floatation, vigorous stirring which may make slag layer exposing an "eye" to air reoxidation should be avoided. After calcium treatment, the inclusions were restricted mainly to globular calcium aluminates and the sulfur in the steel was associated with these inclusions as calcium sulfide. The ND (number density) of inclusions seems to appear a similar tendency to the size distribution of smaller inclusions, and the similar change between the AF (area fraction) of inclusions and the total oxygen content of the steel can be also found by careful comparison. Predicted inclusion type in the steel were validated with measurement based on samples collected from industrial heats and a reasonable range of Ca content was also given for the experimental steel.